Correlation of Health Literacy With Self Care Management In Hypertension Patients in Level II Hospital Dustira Cimahi - Sinaga, Friska; Clara, Yurike; Widiantoro, Fransiskus Xaverius (Open Access Health Scientific Journal, 2024)
Background: Knowledge and self-care management are needed to control blood prreasure among hypertension population. This study aimed to identify correlation between health literacy and self-care management among patient with hypertension in the Dustira Hospital.Methods: Quantitative methods with cross-sectional approach was used in this study. Totally 177 patients with hypertension participated in this study by complete a questionnaire. The European health literacy questionnaire (HLS-EU-Q16) was used to assess health literacy and the hypertension self-management behavior questionnaire (HSMBQ) to measure self-care management. Pearson product moment was used to analyse the correlation of two variables.Results: The results showed that the average score of self care management = 69.80 and health lietaracy = 12.33. Health literacy was statisticaly significant correlate with self care management (p=0.000). The direct of correlation was positive, which it means higher the health literacy; it will improve the self-care management. The strength of the correlation is moderate criteria (r = 0.428)Conclusion: These results could used as data for hospitals to develope training programs for improving health literacy and self care management.